2022
DOI: 10.3390/ijerph19148804
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Moroccan COVID-19 Survivors: A Case-Control Study

Abstract: Background: Research on COVID-19 has mostly focused on transmission, mortality and morbidity associated with the virus. However, less attention has been given to its impact on health-related quality of life (HRQoL) of patients with COVID-19. Therefore, this study aimed to determine the demographic and clinical risk factors associated with COVID-19 and evaluate its impact on the HRQoL of COVID-19 survivors. Methods: A case-control study was carried out between September 2021 and March 2022 on 1105 participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…A previously published meta-analysis study stated that 58% of COVID-19 patients reported having a poor quality of life after recovery [ 8 ]. Our observed EQ-5D-5L scores after recovery were similar to figures reported in China (0.949), yet higher than those reported in Morocco (0.86), the UK (0.714), Norway (0.690), and Belgium (0.620) [ 24 , 25 , 26 , 27 , 28 ]. Saudis were able to resume their normal physical activity and fully attend to their self-care needs.…”
Section: Discussionsupporting
confidence: 86%
“…A previously published meta-analysis study stated that 58% of COVID-19 patients reported having a poor quality of life after recovery [ 8 ]. Our observed EQ-5D-5L scores after recovery were similar to figures reported in China (0.949), yet higher than those reported in Morocco (0.86), the UK (0.714), Norway (0.690), and Belgium (0.620) [ 24 , 25 , 26 , 27 , 28 ]. Saudis were able to resume their normal physical activity and fully attend to their self-care needs.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies examined anxiety and depression among nurses battling COVID-19. 1,2 Medical professionals who actively treat COVID-19 patients, such as doctors and nurses, have been the subject of research to look at the relationship between perceived risk and problems connected to mental health. [3][4][5] In addition to providing useful advice for leading active lifestyles during pandemics, the study assesses whether the sense of control mediates the good benefits of physical exercise on positive or negative mental health under unforeseen unexpected situations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the main focus has been put on preventing and treating the acute phase of the disease, attention is increasingly shifting to the prolonged effects experienced by the survivors, particularly healthcare workers [ 4 ]. Among the multitude of challenges the healthcare workers face, two critical aspects have emerged as paramount: the quality of life (QoL) and the persistent symptoms of dyspnea [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%